TRADISI PEMBERIAN UANG MASUK KAMAR DALAM PERSPEKTIF HUKUM ISLAM (Studi Kasus Pernikahan Dalam Masyarakat Nagari Taluak Tigo Sakato Kecamatan Batang Kapeh Kabupaten Pesisir Selatan) - Duhriah Duhriah; Suhaila Ulfa (UIN Imam Bonjol Padang, 2021)
This study was initiated by the discovery of many people's habits of carrying out a tradition after marriage, known as the giving of room-entry money, which was carried out in Kenagarian Taluak Tigo Sakato, Batang Kapeh District. The research questions in this study are. First, how is the implementation of the money- in-room tradition in Kenagarian Taluak Tigo Sakato, Batang Kapeh District, Pesisir Selatan Regency. Second, what is the impact of not fulfilling the tradition of giving money into the room. Third, what is the public's view of the tradition of giving money into the room. Fourth, how is the review of Islamic law on the provision of money into the room. This type of research is a field research by collecting the results of interviews with men, ninik mamak, families who are present in the implementation of this tradition. The results of this study are: first, the implementation of the tradition of giving room entry money in Kenagarian Taluak Tigo Sakato, Batang Kapeh District, is carried out at the bride's house which is handed over by the man to the woman after the marriage contract is carried out. The second impact of not fulfilling the tradition of giving money into the room is that the groom is not allowed to enter the bridal chamber. The three public responses to the tradition of giving money into the room have positive and negative responses. The positive response is that the people in Kenagarian Taluak Tigo Sakato support and accept this tradition of giving money to the room rather than being ostracized by the community. While the negative response is that there are people who object to the tradition of giving money into this room but they still do it with a heavy heart. The fourth review of Islamic law on the provision of room entry fees is urf sahih because it does not conflict with religion and aims to maintain the benefit of society